2012
DOI: 10.1074/jbc.m111.337949
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of Matrix Metalloproteinase-2 (MMP-2)

Abstract: Background: Matrix metalloproteinase-2 (MMP-2) activity is regulated by several mechanisms. Results: We observed that Ca 2ϩ ion is essential for MMP-2 homodimerization, which in turn results in the proteolysis of small peptide substrates and enhances thrombin-mediated activation of pro-MMP-2. Conclusion: Pro-MMP-2 activation is modulated by MMP-2 homodimerization. Significance: This study elucidates a novel mechanism to regulate MMP-2 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…Immunoblotting showed increase in MMP‐2 expression in the CR and MILD phenotypes compared with sham and was further increased in the MOD phenotype compared with sham, CR, and MILD. Furthermore, there was increase in the dimerization of MMP‐2 in the MOD phenotype, which has been shown to correlate with increased MMP‐2 activity24 (Figure 5A). MMP‐9 expression was increased and TIMP‐1 expression was decreased in the MOD phenotype only (Figure 5A).…”
Section: Resultsmentioning
confidence: 83%
“…Immunoblotting showed increase in MMP‐2 expression in the CR and MILD phenotypes compared with sham and was further increased in the MOD phenotype compared with sham, CR, and MILD. Furthermore, there was increase in the dimerization of MMP‐2 in the MOD phenotype, which has been shown to correlate with increased MMP‐2 activity24 (Figure 5A). MMP‐9 expression was increased and TIMP‐1 expression was decreased in the MOD phenotype only (Figure 5A).…”
Section: Resultsmentioning
confidence: 83%
“…Also, in cultured rat cardiomyocytes, treatment with IgG obtained from preeclamptic women enhances AT 1 R-mediated response, which is ameliorated with the PKC inhibitor calphostin C, further supporting a role of PKC in preeclampsia [87]. Studies have also shown that EGF and PKC could promote MMP dimerization [28]. The present study support a role of EGFR/PKC pathway in the observed MMP-9 homodimerization because: 1) In placenta, uterus, and uterine artery of Preg rats, treatment with EGFR inhibitor or PKC inhibitor reduced the gelatinolytic activity of 200 kDa MMP-9 homodimer.…”
Section: Discussionmentioning
confidence: 99%
“…Also, MMPs are often secreted in an inactive pro-form that undergoes proteolytic activation by other MMPs and proteases to the active form [18, 25]. MMP-2 could undergo dimerization and form complexes with other MMPs or even TIMPs [2832, 3538]. Also, MMP-9 may undergo homodimerization as well as complexation with other proteins [33, 34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations